A comparative study between trans-rectal ultrasound guided 6-core and 12- core prostate biopsy for detection of prostate cancer (Bangladesh Journal of Urology, 2012)
Purpose: This study was perform to assess the comparative accuracy of trans-rectal ultrasound guided 6-core verses 12- core prostate biopsy for detection of prostate cancer. Materials and Methods: A prospective comparative study between 6 cores and 12 cores prostate biopsy was done by a prospective comparative study from July 2007 to June 2008 in urology outpatient department, Bangabandhu Sheikh Mujib Medical University, Dhaka Medical College Hospital, Popular diagnostic Centre, Dhaka and Comfort Nursing Home, Dhaka. Study population included the patients having raised serum PSA or abnormal DRE attending in the above centres. They were divided into two groups. Group A was scheduled for 6 cores biopsy and Group B for 12 cores biopsy. A total 60 patients of PSA >4ng/ml or abnormal DRE or both were selected for prostate biopsy. Results: In this study prostate cancer detection rate in 6 core prostate biopsy (Group-A) was 20% and in 12 core prostate biopsy (Group-B) was 46.67%. This study showed significant difference between the two procedures in respect of cancer detection. The 12 cores TRUS-guided prostate biopsy improved the detection rate of prostate cancer by 26.67% when compared with the traditional 6 cores biopsy technique without increasing in the morbidity. Conclusions: The results of this study shown that the cancer detection rate is higher in transrectal ultrasound guided 12 cores prostate biopsy than transrectal ultrasound guided 6 cores prostate biopsy without increasing the morbidity.BJU 2010; 13(1): 14-20